Pentingnya Pendidikan Karakter Di Tingkat SMP Pada Era Globalisasi - Fariz Aditya; Florensia Silaban; Raja Songkup Pratama; Putri Aprilya; Rahmi Siregar; Jamaludin Rumi (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
Character education at the junior high school level is becoming increasingly important in this era of globalization. This research aims to explore the influence of globalization on the development of adolescent character at the junior high school level and to identify character values relevant to the demands of globalization. The research method used is a qualitative approach through literature review with descriptive analysis techniques. The findings of the research indicate that globalization has a significant impact on the development of adolescent character at the junior high school level, particularly in how adolescents express themselves, their mindset, and the values they adhere to. In this context, it is important to teach character values such as tolerance, diversity, cooperation, and critical thinking, which are relevant to the demands of globalization. Effective strategies for integrating character education into the junior high school curriculum include developing a curriculum based on character values, teacher training, and active involvement of parents and the community. Thus, character education at the junior high school level can become relevant to the demands of globalization and help adolescents build strong and adaptive characters.